Money supply and inflation in Europe: Is there still a connection? - Matthias Diermeier; Henry Goecke (Institut der deutschen Wirtschaft (IW), 2016)
Since the outbreak of the European financial and economic crisis in 2008, the monetary policy of the European Central Bank (ECB) has been in crisis mode. The central bankers are attempting to get a grasp on the current low inflation rates and inflation expectations by, among other things, introducing a policy of extreme quantitative easing. The expansion of the Eurosystem's balance sheet was problem-free on this occasion, and the ECB also managed to eventually increase the money supply again. However, ensuring that the growth in the money supply transmutes into higher inflation or inflation expectations has been much more difficult. [...] – – Seit dem Ausbruch der europäischen Finanz- und Wirtschaftskrise im Jahr 2008 befindet sich die Geldpolitik der Europäischen Zentralbank (EZB) im Krisenmodus. Die Übersetzung der wachsenden Geldmenge auf eine höhere Inflation beziehungsweise Inflationserwartung gestaltet sich schwierig. Den aktuell niedrigen Inflationsraten und Inflationserwartungen versuchen die Zentralbanker unter anderem mit einer Geldpolitik extremer quantitativer Lockerung habhaft zu werden. Die Bilanzausweitung des Eurosystems ging hierbei problemlos von statten, und auch die Erhöhung der Geldmenge gelang der EZB zuletzt wieder. Allerdings gestaltet sich die Übersetzung der wachsenden Geldmenge auf eine höhere Inflation beziehungsweise Inflationserwartung als weitaus schwieriger. [...]
Keywords: E31; E52; E58; 330